Inhibition of Demineralization of Dentin by Fluoride-Containing Hydrogel Desensitizers: An In Vitro Study - Yasuhiro Matsuda; Bayarchimeg Altankhishig; Katsushi Okuyama; Hiroko Yamamoto; Katsuaki Naito; Mikako Hayashi; Hidehiko Sano; Sharanbir K. Sidhu; Takashi Saito (Journal of Functional Biomaterials, 2022)
Several desensitizers routinely used clinically for dentin hypersensitivity are expected to inhibit demineralization. This study aimed to evaluate the effectiveness of sealing materials in inhibiting demineralization and increasing fluorine (F) uptake by acid-treated root surfaces. Five noncarious extracted human teeth were used to produce specimens. Three different fluoride-containing materials, namely “MS Coat F” (MS), “MS Coat Hys Block Gel” (HS), and CTX2 Varnish (FV), were used herein. Each material was applied to the demineralized root surface. Single sections were obtained from each specimen. All surfaces of each specimen, except the polished surface, were covered with wax and immersed in an automatic pH cycling system for 2 weeks. Fluorine and calcium distributions in the carious lesions of each specimen were evaluated using proton-induced gamma emission (PIGE) and X-ray (PIXE) techniques, respectively. Dentin demineralization was analyzed using transverse microradiography (TMR) before and after pH cycling. µPIXE/PIGE analysis demonstrated that all sample groups showed increased fluoride uptake on the root surface. TMR analysis revealed that both HS and FV showed significantly lower integrated mineral loss values than the control group. All three samples demonstrated a tendency towards increased fluoride uptake from fluoride-containing hypersensitivity desensitizers and a demineralization inhibition effect on root dentin.